Crawling PubMed with web agents for literature search and alerting services - Carvalhal, Carlos (2013)
In this paper we present ASAP - Automated Search with Agents in PubMed, a web-based service aiming to manage and automate scientific literature search in the PubMed database. The system allows the creation and management of web agents, parameterized thematically and functionally, that crawl the PubMed database autonomously and periodically, aiming to search and retrieve relevant results according the requirements provided by the user. The results, containing the publications list retrieved, are emailed to the agent owner on a weekly basis, during the activity period defined for the web agent. The ASAP service is devoted to help researchers, especially from the field of biomedicine and bioinformatics, in order to increase their productivity, and can be accessed at: http://esa.ipb.pt/~agentes.